Poverty impacts of widely adopted CGIAR innovations - Laborde Debucquet, David; Martin, Will; Tokgoz, Simla; Lallemant, Tess; Majeed, Fahd (International Food Policy Research Institute, 2017)
This study attempts to measure the impact of the CGIAR on global poverty, first by utilizing two different approaches to measuring the impact of CGIAR research and development (R&D) on agricultural productivity and then by using models for 300,000 households to assess the impacts of these productivity gains on poverty at a global level. Since it was founded in 1971, the CGIAR has mobilized funding, largely from aid agencies and private foundations, to raise global agricultural productivity, particularly by smallholder farmers in developing countries. While the period 1990–2010 saw reduced support for the CGIAR and for global research and development in agriculture, in recent years, the CGIAR has invested over $900 million annually.